Efeito da densidade populacional sobre as curvas de crescimento de Macrobrachium rosenbergii (De Man) em cultivo semi-intensivo (Crustacea, Palaemonidae) - Valenti, Wagner Cotroni [UNESP] (1993)
In this article the length growth curves of Macrobrachium rosenbergii (De Man, 1879) held in different population densities were analysed. Postlarvae prawns were stocked into five 0,02 ha earthen ponds at densities of 4, 8, 12, 16 and 20 ind./m² during six months. Forthnightly, the mean total length of animals from each pond were obtained by means of random samples. For each population the length growth curves and the instantaneous growth rate expressions were determined. The growth rate and the asymptotic maximum length decreased with the stocking density raised. This effect is greater when the density ranges in low levels. The growth decrease can be due to intraspecific competition for life resources and to negative interactions between individuals, as aggressive or social behavior, that increase with the increase prawns density.